Dual-Route Distribution Strategy with Supply Chain Disruption. Issue 1 (January 2014) - Hur, Sung Ho; Kim, Dong-Kyu; Kho, Seung-Young; Lee, Chungwon
Unexpected disruptions in the supply chain can directly and indirectly cause additional logistics costs because of delayed delivery. Previous studies have minimized the additional cost with a network design that used the concept of level of service and unit delay cost; however, in cases of disruption in a regional distribution center (RDC), companies commonly must secure a bypass through another RDC and pay more to use a faster transportation mode. The aim of this study is to develop a dual-route distribution strategy to minimize the logistics costs that stem from the disruption in the RDC. The model addressed in this study determines the RDC allocation and the freight dualization ratio to establish a bypass before a disruption occurs and to ensure the punctuality of delivery without losses due to late delivery. An application of the model uses an actual company's network data. The results of this application show that the dual-route distribution strategy can be more advantageous than a single-route distribution strategy. The model provides a theoretical basis for the use of the dual-route strategy to minimize the direct and indirect costs associated with the RDC disruption.